IMPACT OF LEADERSHIP STYLE AND WORK CONFLICT ON PERFORMANCE IN THE MEDICAL FIELD AND HEALTH OF NORTH SUMATERA REGIONAL POLICE THROUGH JOB SATISFACTION - Cynthia Rut Vio Nanda Tarigan; Paham Ginting; Yeni Absah (CV. Radja Publika, 2024)
Employee performance in a government organization is an important component in achieving the goal of providing the best service to the community. As a result, leaders must effectively handle work conflicts that affect employee performance and job satisfaction. This research aims to analyze the influence of leadership style and work conflict on performance in the field of medicine and health in the North Sumatra Regional Police, as well as through job satisfaction. Leadership style and work conflict are identified as factors that influence individual performance in the organizational context. Data was collected through a survey using a questionnaire distributed to 83 respondents in the North Sumatra Regional Police's Biddokkes. Data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. The research results show that leadership style has a positive and significant influence on performance in the field of medicine and health in the North Sumatra Regional Police. Work conflict has a negative and significant effect on performance. High work conflict tends to hinder individual performance. Job satisfaction can mediate the relationship between leadership style, work conflict, and performance. This means that if individuals feel satisfied with their work, the negative influence of work conflict can be reduced and the positive influence of leadership style can be increased. This research provides an important contribution to the understanding of the factors that influence performance in the field of medicine and health in the North Sumatra Regional Police. The practical implication of this research is the importance of developing an effective leadership style and good conflict management in improving individual performance. Apart from that, organizations also need to pay attention to job satisfaction as a factor that can mediate the relationship between leadership style, work conflict and performance.